A randomized controlled trial of Eye Movement Desensitization and Reprocessing (EMDR) Therapy in the treatment of fibromyalgia - Zat Çiftçi, Zeynep; Delibaş, Dursun Hakan; Kaya, Taciser; Külcü, Duygu Geler; Sarı, Aylin; Nazlıkul, Hüseyin; Coşkun Topsakal, İlkem; Aydın, Yunus Emre; Kavakçı, Önder; Savran, Canan; Konuk, Emre (Frontiers in Psychiatry, 2024)
Background In addition to pharmacological treatment, psychotherapeutic approaches are recommended for the treatment of fibromyalgia. There is a suggestion that eye movement desensitization and reprocessing (EMDR) therapy may be effective. This study aimed to investigate the impact of EMDR therapy on fibromyalgia symptoms, depression, sleep quality, and traumatic stress in fibromyalgia patients through a randomized controlled study (RCT). Materials and methods The sample for this study comprised 79 individuals diagnosed with fibromyalgia. Participants were randomly assigned to two groups: the “Treatment as Usual” (TAU) group and the TAU + EMDR group. Prior to the study and at six different time points (before starting the study, at the end of the 5th, 10th, and 15th sessions, 1 month later, and 3 months later), participants completed assessments, including the Fibromyalgia Impact Questionnaire (FIQ), Visual Analog Scale (VAS), Fibromyalgia ACR 2010 Diagnostic Criteria [Widespread Pain Index (WPI) and Symptom Severity Scale (SSS)], Beck Depression Inventory (BDI), Pittsburgh Sleep Quality Index (PSQI), and Trauma Symptom Checklist-40 (TSC-40). Results There were no differences in the sociodemographic variables between the study and experimental groups. Analysis of variance revealed a statistically significant group effect on VAS (p = 0.019), WPI (p = 0.018), BDI (p = 0.019), and TSC-40 (p = 0.21). After applying Bonferroni correction, EMDR was found to be effective for VAS, WPI, SSS, BDI, PSQI, and TSC-40 (p <0.05). Conclusion The results of the current study suggest that EMDR therapy is a viable alternative treatment for fibromyalgia. We believe these findings offer robust evidence supporting the efficacy of EMDR therapy in treating fibromyalgia, particularly in the context of a randomized controlled trial (RCT). The application of EMDR therapy for the treatment of patients with fibromyalgia is likely to be beneficial. Clinical trial registration ClinicalTrials.gov, identifier NCT06265194.